(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Wound healing remains a challenging clinical problem for which precise and efficient management is essential in order to curtail morbidity and mortality. Wound healing has been shown to depend upon the availability of appropriate trace elements like copper and zinc which serve as enzyme cofactors and structural components in tissue repair. This study aims at evaluating the distribution of zinc and copper found in the hair as well as skin during epidermal wound healing. Adult and healthy West African dwarf (WAD) goats of both sexes fed with concentrate, grass, cassava peel and water ad libitum were used. The animals were housed for three weeks before commencement of the experiments. Epidermal wounds were created on the trunks of all the goats using cardboard template of 1cm². Progressive changes in wound contraction were monitored grossly by placing clean and sterile venier calliper on the wound margin. Hair and skin elemental (copper and zinc) analyses were done using atomic absorption spectroscopy (AAS). Significant increases in Cu level were observed in the female hair compared with that of males. There were significant increases in the Zn levels of the females’ hair compared with the males. The wound healed faster in female goat compared with the males. The ratio of copper to zinc is clinically more important than the concentration of either of these trace metals. The pattern of distribution between zinc and copper concentration in the skin and hair of the male and female goats observed in this study could be added factor responsible for early wound healing in female. Therefore, our findings suggest that the distribution in the Cu and Zinc level in skin and hair of both male and female goats could also be a factor for wound healing in the animals.